Retina and Choroid of Diabetic Patients Without Observed Retinal Vascular Changes: A Longitudinal Study - Ferreira, J (2017)
PURPOSE: To identify changes in choroidal thickness (CT) and all retinal layers of diabetic patients without diabetic retinopathy (DR) after 1 year of follow-up. DESIGN: Prospective observational cohort study. METHODS: Overall, 125 diabetic patients without DR were included. Two visits were scheduled: the first visit (V1) and a second visit after 12 months (V2). At both visits, patients received a complete ophthalmologic evaluation that included OCT. Each retinal layer thickness was calculated for 9 ETDRS sectors, and CT was measured at 13 locations. Generalized linear mixed-effects models were used. RESULTS: Of the 125 patients, 103 completed the study, and 9 of the 103 developed DR (8.7%). CT was significantly higher at V2 than at V1, with an average value of 10-17 μm at almost half the locations (500, 1000, and 1500 μm temporal; 500 and 1000 μm nasal; and 1000 μm superior to the fovea) (P < .001-.003). The thicknesses of the ganglion cell layer (I3 and N6 sectors), inner plexiform layer (S6 and N6 sectors), inner nuclear layer (T6 and N6 sectors), and outer plexiform layer (S6 sector), as well as the overall retinal thickness (RT) (S3, N3, I3, S6, and T6 sectors), were decreased at V2 (P < .001). Visible retinopathy was negatively associated with overall RT (central, S3, T3, I3, and N3 sectors, P = .004-.024) and the thickness of the ONL (T6 and I6 sectors, P = .007 and P = .009) and photoreceptor layer (N6 sector, P = .038). The presence of DR decreased the overall RT by 13.04-16.63 μm. CONCLUSIONS: Diabetic patients without DR showed a thicker choroid and a thinner retina, particularly in inner layers, after 1 year of follow-up. These structural changes may correspond to the early neurodegenerative phase of DR.